2003
DOI: 10.1016/s0886-3350(03)00467-x
|View full text |Cite
|
Sign up to set email alerts
|

Optical aberrations of the human anterior cornea

Abstract: Anterior corneal wavefront aberrations varied greatly among subjects and increased slightly with aging. All corneas had positive 4th-order SAs, and the values did not change with aging. A moderate to high degree of mirror symmetry existed between right and left eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
181
2
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(215 citation statements)
references
References 11 publications
17
181
2
10
Order By: Relevance
“…Large ranges of corneal SA in the population have been reported. 5 Therefore, depending on an individual's corneal SA and the SA of the IOL selected, a wide range of residual ocular SA is possible for an eye undergoing IOL implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large ranges of corneal SA in the population have been reported. 5 Therefore, depending on an individual's corneal SA and the SA of the IOL selected, a wide range of residual ocular SA is possible for an eye undergoing IOL implantation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Applegate and colleagues 6 have reported that aberrations in different Zernike terms interact to increase or decrease optical performance. It is unclear what the optimal amount of SA would be in eyes with various HOAs.…”
Section: Introductionmentioning
confidence: 99%
“…Holladay et al 1 reported a mean corneal spherical aberration value of 0.27 µm, which generally agrees with the literature for Caucasian populations. 9,10 These data, on the whole, imply a variability in optical aberrations between ethnic groups, as Japanese eyes seem to have smaller corneal spherical aberration than Caucasian eyes.…”
Section: Discussionmentioning
confidence: 91%
“…8 The use of ocular wavefront-guided treatment may have some limitations as some aberrometers cannot accurately measure eyes with central islands or with severe changes in refractive power across the pupil. 5,9,10 Additionally, the incorporation of lenticular aberrations that are clinically insignifi cant in the optical degradation of an eye that has undergone corneal surgery or trauma results in needless tissue removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation